DAMPAK MOTIVASI DAN KOMPETENSI TERHADAP KINERJA YANG DIMODERASI VARIABEL KEPEMIMPINAN PADA TERMINAL PETIKEMAS DI PELABUHAN BELAWAN - WINDA ARDIANI (JURNAL ILMIAH KOHESI, 2019)
The purpose of study was to analyze the effect of Motivation and Competence on employee performance with the leadership variable as a moderating variabel in the Terminal Petikemas Domestik Belawan. Primary data collection is done through a questionnaire distributed to employees. Data analysis methods using quantitative methods, namely the analysis of Multi Linear Regression and Moderating Regression Analysis. This study are employees at the Terminal Petikemas Domestic Belawan. The samle in this study used 103 respondents. The result showed that Motivation, Competence and Leadership had a positive and significant influence on employee performance at the Terminal Petikemas Domestik Belawan. While leadership ia able to moderate the influence of Motivation and Competence on employee performance in the Terminal Petikemas Domestik Belawan.